Differential stability of bacterial photosynthetic apparatus of Rhodobacter alkalitolerans strain JA916T under alkaline and light environment - Zamal, Mohammad Yusuf; Madireddi, Saikiran; Mekala, Nageswara Rao; Chintalapati, Venkata Ramana; Subramanyam, Rajagopal (Frontiers in Microbiology, 2024)
In purple bacteria, photosynthesis is performed by densely packed pigment-protein complexes including the light-harvesting complexes known as RC-LH1 and LH2 with carotenoids to assist in the well-functioning of photosynthesis. Most photosynthetic bacteria are exposed to various abiotic stresses like light, temperature, alkalinity-acidity, and salinity.Rhodobacter (R.) alkalitolerans discovered from the alkaline pond, here we report the comparative study of the photosynthetic apparatus of R. alkalitolerans in various light intensities in relation to its high pH tolerance ability. With increased intensity, the stability of photosystem complexes decreased in normal pH (npH pH 6.80±0.05) conditions, whereas in high pH (hpH pH 8.60±0.05) acclimation was observed to high light. The content of bacteriochlorophyll a, absorbance spectra, and circular dichroism data shows that the integrity of photosystem complexes is less affected in hpH compared to npH conditions. Large pore blue native polyacrylamide gel electrophoresis of photosystem protein complexes and sucrose density gradient of n-dodecyl β-Dmaltoside solubilized intracytoplasmic membranes shows that LH2 is more affected in npH than hpH, whereas RC-LH1 monomer or dimer has shown interplay between monomer and dimer in hpH although the dimer and monomer both increased in npH. Increased content and expression level of ATPase protein complex and subunit -"c" of ATPase, fast relaxation kinetics of p515, and relatively higher membrane lipid content in hpH along with less photooxidative stress and subsequently lesser superoxide dismutase activity exemplify photoprotection in hpH. Further, the increased expression levels of antiporter NhaD in hpH signifies its role in the maintenance of homeostatic balance in hpH.Light-harvesting complexes (LH1, LH2), High light, Intracytoplasmic membranes, Reaction center-light-harvesting complex (RC-LH1), Rhodobacter alkalitolerans strain JA916 T .